Exploring the Relationship Between Instagram Use and Body Image Issues Among Teenagers - Vidyawati; Siti Rahmawati (Mahogany Journal De Social, 2024)
The purpose of the study is to examine how Instagram usage is associated with the body image anxiety problems in adolescents and how social comparison can mediate the association. The method of the research is quantitative survey and descriptive statistical analysis, Pearson correlation, and linear regression and also qualitative interviews to understand the subjective experiences of Instagram users. The findings of the quantitative study revealed that, the duration of Instagram use and social comparison had significant positive effect on body image anxiety and that social comparison was the primary mediator. Qualitative data show that the teens are usually feeling pressured by unrealistic beauty standards and lower in self-confidence when exposed to social comparison, despite the fact that positive content can offer emotional support. To sum up, the negative influence on the mental health of adolescents should be minimized by implementing interventions based on social media education and promoting positive body images.